Lesotho : Staff Report for the 2001 Article IV Consultation and the Second Review Under the Poverty Reduction and Growth Facility Arrangement and Request for Waiver of Performance Criterion. (IMF Staff Country Reports; Country Report ;, 2002)
This paper examines Lesotho's 2001 Article IV Consultation, Second Review Under the Poverty Reduction and Growth Facility Arrangement, and a Request for Waiver of the Performance Criterion. The economic program remains on track. Key economic indicators are performing as expected, and all quantitative performance criteria for end-September 2001 were observed. However, one structural performance criterion, making the Lesotho Revenue Authority operational, was delayed because of late parliamentary action. One benchmark-completing the 2000/01 public accounts for auditing-was not completed because of a decision to complete accounts from 1993/94 in sequence.